2017
DOI: 10.1111/1365-2664.12902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deer on woodland structure revealed through terrestrial laser scanning

Abstract: 1. Terrestrial laser scanning (TLS) captures the three-dimensional structure of habitats. Compared to traditional methods of forest mensuration, it allows quantification of structure at increased resolution, and the derivation of novel metrics with which to inform ecological studies and habitat management. 2. Lowland woodlands in the UK have altered in structure over the last century due to increased abundance of deer and a decline in management. We compared whole-canopy profiles between woodlands with high (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…Browsing can increase field and shrub layer abundance due to the creation and maintenance of canopy openings (Mcinnes et al 1992) but may also reduce it if browsing occurs on shrubs (Eichhorn et al 2017) or herbs directly (as is the case for this study). We found that moose exclosures greatly increased the biomass of large herbs and ferns (Fig.…”
Section: Understory Vegetationmentioning
confidence: 87%
“…Browsing can increase field and shrub layer abundance due to the creation and maintenance of canopy openings (Mcinnes et al 1992) but may also reduce it if browsing occurs on shrubs (Eichhorn et al 2017) or herbs directly (as is the case for this study). We found that moose exclosures greatly increased the biomass of large herbs and ferns (Fig.…”
Section: Understory Vegetationmentioning
confidence: 87%
“…Many ecosystem functions and services provided by forests, such as biodiversity (e.g., Lindenmayer, Margules, & Botkin, 2000), productivity (e.g., Ishii, Tanabe, & Hiura, 2004), habitat suitability (Eichhorn et al, 2017;MacArthur & MacArthur, 1961;Tilman & Kareiva, 1997), or recreational benefit (e.g., Ribe, 2009) as well as ecosystem resilience and adaptability (McElhinny, Gibbons, Brack, & Bauhus, 2005;Neill & Puettmann, 2013;Schulze, Beck, & Müller-Hohenstein, 2002), are affected by forest structure. Despite this great importance, very little is known about forest structure in all three dimensions and how it is naturally formed and artificially altered.…”
Section: Introductionmentioning
confidence: 99%
“…Successful management aimed at maintaining bird species in woodlands affected by fragmentation needs to ensure there is protection and/or rehabilitation of ground vegetation and overstorey, as pointed out by Montague-Drake et al [65] in relation to temperate woodlands of Australia. In temperate hardwood forests ground vegetation can be seriously disturbed by ungulate browsing with consequences for bird diversity [66] due to the absence of large predators [67]. Thus, we should also take into account ungulate management on the landscape scale [68,69].…”
Section: Discussionmentioning
confidence: 99%